Dampak Pandemi Covid-19 terhadap Pelaksanaan Akad Perkawinan di Kantor Urusan Agama Kecamatan Kabanjahe - Dedy Iskandar Butar-Butar (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
After the enactment of Presidential Decree no. 12 of 2020 and PP no. 21 of 2020 regarding Covid-19 and PSBB, many public services experienced disruption, including marriage services. To avoid crowds at the District KUA, the number of marriage ceremonies is limited to eight couples per day. However, the Kabanjahe District KUA reported an increase in marriage requests in recent times, especially during the pandemic. Therefore, researchers are interested in examining the impact of the Covid-19 pandemic on marriage contracts at the KUA Kabanjahe District in 2022, with a focus on the implementation of Presidential Decree no. 12 of 2020 and PP no. 21 of 2020, especially the principle of mashlahah murlahah, is considered impermissible because it can cause harm or damage to humanity. This legal determination is based on the principle of ushul fiqh which states that "rejecting damage must take precedence over bringing benefit". In this context, the damage referred to is the risk of spreading Covid-19 among the Walimatul 'Ursy participants. Meanwhile, bringing benefit means continuing to carry out walimatul 'ursy as a form of notification to the public about the existence of a bond between the bride and groom's families. Supporting factors for this include good coordination between the KUA and assistants such as the Covid-19 officer unit, health educators and community leaders who are aware of social restrictions. Meanwhile, the inhibiting factor is the lack of public awareness regarding the importance of complying with regulations.